Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1139/y07-017
|View full text |Cite
|
Sign up to set email alerts
|

Non-genomic effects of aldosterone on intracellular ion regulation and cell volume in rat ventricular myocytes

Abstract: Aldosterone has non-genomic effects that express within minutes and modulate intracellular ion milieu and cellular function. However, it is still undefined whether aldosterone actually alters intracellular ion concentrations or cellular contractility. To clarify the non-genomic effects of aldosterone, we measured [Na+]i, Ca2+ transient (CaT), and cell volume in dye-loaded rat ventricular myocytes, and we also evaluated myocardial contractility. We found the following: (i) aldosterone increased [Na+]i at the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
4
20
1
Order By: Relevance
“…On the other hand, ourselves and others have recently reported that aldosterone exerts transient but favorable effects on cardiocytes in vitro, mainly via rapid MR-independent actions (Yamamuro et al 2006, Bunda et al 2009, Nagoshi et al 2012. In agreement with these findings, the present ex vivo study demonstrated the rapid, favorable effects of aldosterone on cardiac functional recovery and injury during ischemia-reperfusion, although aldosterone did not affect the baseline cardiac function (Table 1), congruent with the findings of previous reports by other groups (Fujita et al 2005, Matsui et al 2007). However, our results do not completely agree with the findings of several other studies showing that rapid, MR-independent actions of aldosterone induce positive inotropic effects at baseline (Barbato et al 2002, Chai et al 2005, while the administration of aldosterone results in no significant effects (Chai et al 2005, Schmidt et al 2010, but rather results in detrimental effects (Fujita et al 2005, Mihailidou et al 2009) on cardiac functional recovery and injury after ischemia-reperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, ourselves and others have recently reported that aldosterone exerts transient but favorable effects on cardiocytes in vitro, mainly via rapid MR-independent actions (Yamamuro et al 2006, Bunda et al 2009, Nagoshi et al 2012. In agreement with these findings, the present ex vivo study demonstrated the rapid, favorable effects of aldosterone on cardiac functional recovery and injury during ischemia-reperfusion, although aldosterone did not affect the baseline cardiac function (Table 1), congruent with the findings of previous reports by other groups (Fujita et al 2005, Matsui et al 2007). However, our results do not completely agree with the findings of several other studies showing that rapid, MR-independent actions of aldosterone induce positive inotropic effects at baseline (Barbato et al 2002, Chai et al 2005, while the administration of aldosterone results in no significant effects (Chai et al 2005, Schmidt et al 2010, but rather results in detrimental effects (Fujita et al 2005, Mihailidou et al 2009) on cardiac functional recovery and injury after ischemia-reperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…Nongenomic but MR-independent activation of NHE-1 induced by aldosterone was described previously in the rat heart. 10,11 On the other hand, and in agreement with our data, Michea et al 37 determined that this nongenomic effect of the hormone was mediated by its binding to the MR. More recently, it was reported in vascular smooth muscle that certain nongenomic effects of aldosterone were attributed to simultaneous activation of MR and a surface membrane G protein-coupled receptor, the GPR30. 38 These investigators also reported that the MR pharmacological inhibitors used by us behave as partial antagonists of the GPR30.…”
Section: Discussionsupporting
confidence: 90%
“…NHE1 is not only known for its effects on electrolyte and acid-base regulation but also for its function as a regulator of cytoskeletal function which affects various transport processes, cell motion and cell volume and perhaps also fibronectin synthesis (Markos et al 2005, Leite-Dellova et al 2008, Zhang et al 2010, Braga-Sobrinho et al 2012. Furthermore, NHE1 is also important for other organs like vasculature and heart (Ebata et al 1999, Michea et al 2005, Miyata et al 2005, Matsui et al 2007, De Giusti et al 2011) and a genomic increased NHE1 expression induced by aldosterone has been additionally described in various tissues (Karmazyn et al 2001). In strips of human arteries, aldosterone-induced changes in intracellular pH mediated by NHE1 could be blocked by the MR antagonist RU28318 and could be mimicked by cortisol but only in the presence of an 11beta-hydroxysteroid dehydrogenase 2 inhibitor (Alzamora et al 2000).…”
Section: :1mentioning
confidence: 99%
“…A rapid increase in contractility was detected by some groups after aldosterone treatment in rat isolated working heart (Moreau et al 1996, Barbato et al 2002 while other groups found no effect on contractility or a reduced contractility in human trabeculae (Chai et al 2005, Matsui et al 2007. During ischemia, nongenomic aldosterone effects reduce coronary blood flow and thereby impair cardiac metabolic and contractile function (Fujita et al 2005).…”
Section: Endothelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation